Association of season and herd size with somatic cell count for cows in Irish,English, and Welsh dairy herds - Archer, Simon C.; Mc Coy, Finola; Wapenaar, Wendela; Green, Martin J. (Elsevier, 2013)
The aims of this study were to describe associations of time of year, and herd size with cow somatic cell count (SCC) for Irish, English, and Welsh dairy herds. Random samples of 497 and 493 Irish herds, and two samples of 200 English and Welsh (UK) herds were selected. Random effects models for the natural logarithm of individual cow test day SCC were developed using data from herds in one sub-dataset from each country. Data from the second sub-datasets were used for cross validation.